Psychology in prisons - Crighton, David A. (A BPS Blackwell book, 2008)
Edited by the Head of Psychology for HM Prison Service and the National Probation Service, and fully updated to take account of structural changes within these Services, Psychology in Prisons takes an in-depth look at the work of psychologists in prisons strengthened by in-depth consideration of diversity issues such as age, gender, socio-economic group, sexuality and ethnicity. Focuses exclusively on the prison environment and prioritises practical information for practitioners working in prisons. Contextualises psychological work in prisons, and covers evidence based practice in key areas such as drug misuse and sex offending. Focused on the needs of the client group. Features a section on the practicalities of psychological assessment and interventions